Personal empowerment among Al-Anon/Nar-Anon members in Iran - Ajri, Zahra; Sabran, Mohammad Shatar (Marsland Press, 2011)
As addiction affects not only on addict person but also on family members, so relationship behaviors is an important part of codependents’ life which needs to recover in order to achieve health promotion. This study investigates to find whether the "12-Step Program" empowers families of addicts/alcoholic in term of relationship with others or not. In other words, this study aims to find differences of relationship behaviors by comparing families of addicts/alcoholics who practice the "12-Step Program" and who do not. Theory of empowerment is the key theory to conduct this study. The findings of this study indicate that the “12-step program” is an effective program to enables codependents to improve their relationship with others in comparison with those who do not practice this program (control group). In other words, independent samples t-test reveals that codependents’ relationship behaviors are recovered duo to practicing the "12-Step Program" in Al-Anon/Nar-Anon groups in Iran.